Collective Memory and State’s Stigmatization of Ex-Political Prisoners on G-30S in 1965 - Hamdan T Atmaja (IHiS (Indonesian Historical Studies), 2019)
The state as an institution that holds power has an obligation to protect the public interest. However, power is often used to shackle public interest. In the context of the Thirtieth of September Movement (G30S) in 1965, the state has the power to build a collective memory of the incident. The state even led the community to stigmatize the ex-political prisoners of the Communist Party of Indonesia (PKI). Through an oral history approach, this research attempts to reveal the collective memory and stigmatization of ex-political prisoners of PKI, as well as how history must make peace with the G30S incident. This research elaborates on the collective memory of ex-political prisoners of PKI on the incident that has put them as political victims due to the state’s stigmatization. The stigma destroyed ex-political prisoners, both politically and socially. The collective memory and stigma are very contradictory to the meaning of G30S built by the New Order. For this reason, ex-political prisoners of PKI and the state need to go through a dialogue process that results in an agreement that the incident should not be repeated. It can be done if there is a reconciliation of the past.